Modulation of immune responses on mucosal surfaces through vaccination and dietary intervention - Henderson, Angela J., author; Dow, Steven, advisor; Schenkel, Alan, committee member; Biller, Barbara, committee member; Gonzalez-Juarrero, Mercedes, committee member (Colorado State University. Libraries, 2011)
Numerous pathogenic organisms enter the body at the mucosal surfaces and therefore the mucosal immune response must function as the first line of defense. The ability of the body to induce protective immune responses on the mucosal surfaces is a powerful strategy for the prevention of disease. Therefore, understanding the mechanism of induction associated with protection is critical if there is to be improvement in current treatments. In these studies, the use of vaccination and diet were investigated as potential strategies for the induction of potent immune responses on the mucosal surfaces. The principle of vaccination has been used successfully for centuries. However, there is still a great need for the development of vaccines against mucosal pathogens such HIV, TB, and newly emerging pathogens. The primary way to improve mucosal vaccination is through the use of a potent vaccine adjuvant. The first part of this project focuses on the use of cationic-liposome plasmid DNA complexes (CLDC) as a mucosal vaccine adjuvant for enhancing the immune response to both particulate and soluble antigens. In these studies, intranasal vaccination using CLDC resulted in a balanced humoral and cellular immune response capable of protecting against a lethal pulmonary bacterial challenge. We found that mucosal immunization with CLDC adjuvant resulted in the increase in the pro-inflammatory cytokines IL-6 and IFN-γ. Also, cellular immune responses were shown to be dependent on MyD88 signaling. Finally, resident airway myeloid dendritic cells (DC) efficiently phagocytosed the CLDC adjuvant and efficiently trafficked the associated antigen to the draining lymph node. Therefore the effectiveness of CLDC as a mucosal vaccine adjuvant appears to depend on strong cytokine induction and efficient antigen presenting cell activation and migration. In a similar manner, dietary modulation has been shown to significantly impact the intestinal immune environment and has only recently begun to be investigated. It represents a novel approach for enhancing protective responses against pathogens and inflammatory diseases. The focus of the second part of this study is the ability of dietary rice bran to modulate the mucosal immune response as a potential mechanism to prevent disease. We found that a diet containing 10% rice bran resulted in an increase in local IgA concentrations and surface expression of IgA on mucosal B cells. Also, dietary rice bran induced a significant increase in myeloid dendritic cells residing in the lamina propria and mesenteric lymph nodes, and increased the colonization of native Lactobacillus, a beneficial gut microorganism known for its ability to positively influence the mucosal immune system. This work has increased our knowledge of the impact of vaccination and dietary modulation for the protection of the mucosal surfaces. More specifically, these findings have revealed that CLDC is a potent vaccine adjuvant and that incorporating rice bran in a balanced diet can augment the mucosal immune environment.
Keywords: dendritic cell; rice bran; innate immunity; Lactobacillus